2011
DOI: 10.1007/s10886-011-9921-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Condensed Tannin Structure on Rate of Microbial Mineralization and Reactivity to Chemical Assays

Abstract: We examined how tannin structure influences reactivity in tannin assays and carbon and nitrogen mineralization. Condensed tannins from the foliage of ten tree and shrub species and from pecan shells (Carya illinoensis) had different proportions of: (a) epicatechin (cis) and catechin (trans) isomers, (b) procyanidin (PC) and prodelphinidin (PD) monomers, and (c) different chain lengths. The response of each tannin to several widely used tannin assays was determined. Although there was some variation in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…However, tannins in Norway spruce needles, which contain predominantly procyanidins, and tannins in Scots pine needles, which consist mostly of prodelphidines, did not have very different effects on microbial biomass or rates of C and net N mineralization (Kanerva and Smolander 2008). Moreover, Norris et al (2011) who studied condensed tannins from six different plant species was not able to demonstrate any clear and consistent effects of tannin structure on C and N mineralization rates in soil. They stated that a problem in developing better structure-function relationships is that the tannin preparations are not typically single pure compounds and the derived structural parameters are averages.…”
Section: Tannins Affect Soil Microbial Processes In Several Ways and mentioning
confidence: 89%
See 2 more Smart Citations
“…However, tannins in Norway spruce needles, which contain predominantly procyanidins, and tannins in Scots pine needles, which consist mostly of prodelphidines, did not have very different effects on microbial biomass or rates of C and net N mineralization (Kanerva and Smolander 2008). Moreover, Norris et al (2011) who studied condensed tannins from six different plant species was not able to demonstrate any clear and consistent effects of tannin structure on C and N mineralization rates in soil. They stated that a problem in developing better structure-function relationships is that the tannin preparations are not typically single pure compounds and the derived structural parameters are averages.…”
Section: Tannins Affect Soil Microbial Processes In Several Ways and mentioning
confidence: 89%
“…Condensed tannins of spruce needles contain more procyanidin units while pine needles contain more prodelphinidin units (Maie et al 2003;Kraus et al 2004a;Kanerva et al 2006;Norris et al 2011). …”
Section: Occurrence Of Phenolic Compounds In Plants and Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…This anti-nutritional factor can affect shrimp growth. Tannins are a highly diverse class of plant secondary phenolic compounds (Kraus et al, 2003;Norris et al, 2011) and have been found to interfere with the digestibility of proteins, carbohydrates, and the availability of vitamins and minerals (Liener, 1994). The tannin content (all treatments) of Lemna sp.…”
Section: Discussionmentioning
confidence: 99%
“…In Populus balsamifera growing in the Alaskan taiga, Schimel et al (1998) attributed major changes in soil N-cycling to the secondary compounds found in poplar leaves; poplar litter reduced N-fixation, decomposition, and N-mineralization, while increasing N-immobilization. Some reports indicate that this inhibition of N-cycling can be qualified by the molecular weight of condensed tannins, the vegetative history of the soil, and by the microbial community present (Fierer et al, 2001; Triebwasser et al, 2012); however, research in other types of plant litter has found some of these influences to be inconsistent (Norris et al, 2011). …”
Section: Introductionmentioning
confidence: 99%